Pathophysiological Advantages of Spontaneous Ventilation - Lantos, Judit; Németh, Tibor; Barta, Zsanett; Szabó, Zsolt; Paróczai, Dóra; Varga, Endre; Hartmann, Petra (Frontiers in Surgery, 2022)
Surgical procedures cause stress, which can induce an inflammatory response and reduce immune function. To moderate the surgical stress after video-assisted thoracic surgery, non-intubated thoracic surgery (NITS) was developed as a thoracic procedure. This article reviews the pathophysiology and immune advantages of the NITS procedure and its potential for reducing the negative effects of mechanical one-lung ventilation (mOLV). In the spontaneous ventilation NITS procedure, the negative side effects of mOLV are prevented or reduced, including volutrauma, biotrauma, systemic inflammatory immune responses, and compensatory anti-inflammatory immune responses. The proinflammatory and anti-inflammatory cytokines released from accumulated macrophages and neutrophils result in injury to the alveoli during mOLV. The inflammatory response is lower in NITS than in relaxed-surgery cases, causing a less-negative effect on immune function. The elevation of the leukocyte number and reduction of the lymphocyte number in NITS is more moderate than in relaxed-surgery cases. The ventilation/perfusion match is better in spontaneous one-lung ventilation than in mOLV, resulting in better oxygenation and cardiac output. In mechanical ventilation, the intrathoracal pressure and lung volume are increased, and it has a negative effect on the atrial filling (preload) and cardiac output. Postoperative cognitive dysfunction is also reduced in NITS cases, although this is based on clinical observations and is currently not supported by research studies. The direct effect of relaxant drugs on the acetylcholine receptors of macrophages can cause cytokine release, which is lower in NITS.